Implementasi Metode Total Quality Management (TQM) pada Industri dan Organisasi - Mala Septiani; Risma Indriyanti; Teku Dede Ariyanto; Dian Ayu Puspita; Safuan Safuan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Total Quality Management (TQM) is considered a successful management method to improve total quality in various industries and organisations. Total Quality Management focuses on customer satisfaction, involvement of all stakeholders, data collection and analysis, decision-making based on available evidence, and continuous improvement maintenance. Total Quality Management is considered as a quality control method to improve overall performance in various fields. Data analysis methods were used in conducting this research.